Urban spaces and the complexity of cities. - (:unkn) unknown (Böhlau, 2018)
For some time the "Commission Internationale pour l Histoire des Villes" has been working actively on the comprehensive topic of urban space which is also the aim of this book - result of conferences in Lisbon (2013) and in Clermont-Ferrand (2014). Two thematic priorities are presented in this combined English and French speaking volume: on the one hand cultural-symbolic spaces, on the other hand complexity of urban districts which formed in spite of all diversities collective cities (such as Clermont-Ferrand). Continuous transformation of urban space and dichotomy shaped cities: Cities can be understood as space of town rulers, but also as space of a growing "bohème", but you will find also neighbourhood of Jewish and Muslim quarters.
Keywords: Stadtgeschichte; Stadtforschung; Stadtentwicklung; Stadtstruktur; Stadtraum; Raumnutzung; Öffentlicher Raum; Kultur; Kultureinrichtung; Stadtviertel; Stadtgründung; Raumaneignung; Kulturleben; Stadtgesellschaft; Stadtbewohner; Frühe Neuzeit